Marine Microalgae–Microorganism Co-Cultures: An Insight into Nannochloropsis sp. Use and Biotechnological Applications - Marta Vala Esteves; Diana M. C. Marques; Joana D. de Almeida; Nuno Torres Faria; Frederico Castelo Ferreira (Foods)
The increasing demand for sustainable, economical, and environmentally friendly solutions has positioned microalgae as promising candidates in biotechnology, particularly in food, feed, nutraceutical, pharmaceutical, biofuel, and bioremediation applications. This review explores the role of the Nannochloropsis genus and other marine oleaginous microalgae in co-cultivation systems, highlighting their mechanisms of interaction with various microorganisms and their potential for various biotechnological purposes. Case studies of Nannochloropsis sp. co-cultures with other microalgae, bacteria, and fungi are presented. The different types of associations are described as alternative strategies to enhance biomass productivity, lipid accumulation, and nutrient recycling. A key focus of this review is the potential of Nannochloropsis microalgae co-cultivation in food, as it is part of the list of microalgae to be approved for consumption in the European Union, discussing their rich nutritional value, safety, and regulatory status. Additionally, the role of microalgae in the alternative protein sector is explored, with particular emphasis on their integration in cultivated meat products as nutrient suppliers and metabolic partners for animal cells. Despite their potential, several challenges, such as scale-up, contamination risk, and strain selection, remain key obstacles to the widespread adoption of microalgal biotechnology. Future research should focus on optimizing microalgae-based co-cultures for food applications, addressing safety concerns, and further investigating their integration into functional foods and cellular agriculture products.